Microsoft exchange server 2013 high availability design a highly available Exchange 2013 messaging environment using real-world examples - Mota, Nuno (Packt Pub., 2014)
This book is a hands-on practical guide that provides the reader with a number of clear scenarios and examples, making it easier to understand and apply the new concepts. Each chapter can be used as a reference, or it can be read from beginning to end, allowing consultants/administrators to build a solid and highly available Exchange 2013 environment. If you are a messaging professional who wants to learn to design a highly available Exchange 2013 environment, this book is for you. Although not a definite requirement, practical experience with Exchange 2010 is expected, without being a subject.
Includes index. - Online resources; title from thumbnail of cover on resource description page (Safari, viewed March 06, 2014)
Keywords: Microsoft Exchange server; Electronic mail systems; Client/server computing; Electronic mail messages; Courrier électronique; Architecture client-serveur (Informatique); electronic mail; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference